MODERASI BERAGAMA DAN PEMBANGUNAN MANUSIA DI WILAYAH IBU KOTA NUSANTARA (IKN) - Mukhtar, Mukhtar (Ibn Khaldun University, Bogor, 2024)
The Archipelago Capital (IKN), envisioned as a city of the future not only for Indonesia but for the world, has captured widespread attention. Located in East Kalimantan, IKN has sparked both support and opposition from various groups. Supporters believe thatIKN will enhance the local economy, while opponents argue that it will harm the environment and threaten cultural traditions. One major concern with large-scale migration to IKN is the potential for conflicts between newcomers and local residents. This study adopts a library research approach, drawing data from primary literature on IKN and religious moderation, as well as other supporting sources. The data is then analyzed to formulate insights relevant to addressing challenges associated with the establishment of IKN. The findings indicate that IKN has the potential to trigger conflict; thus, a religious moderation approach is essential for mitigation. Key approaches include fostering national integration of religion and culture, educating about moderation values through religious teachings, and using symbols that embody the principles of religious moderation.